Agent Orange : history, science, and the politics of uncertainty - Martini, Edwin A., 1975- (Culture, politics, and the Cold War., 2012)
"Taking on what one former U.S. ambassador called "the last ghost of the Vietnam War," this book examines the far-reaching impact of Agent Orange, the most infamous of the dioxin-contaminated herbicides used by American forces in Southeast Asia. Edwin A. Martini's aim is not simply to reconstruct the history of the "chemical war" but to investigate the ongoing controversy over the short- and long-term effects of weaponized defoliants on the environment of Vietnam, on the civilian population, and on the troops who fought on both sides. Beginning in the early 1960s, when Agent Orange was first deployed in Vietnam, Martini follows the story across geographical and disciplinary boundaries, looking for answers to a host of still unresolved questions. What did chemical manufacturers and American policymakers know about the effects of dioxin on human beings, and when did they know it? How much do scientists and doctors know even today? Should the use of Agent Orange be considered a form of chemical warfare? What can, and should, be done for U.S. veterans, Vietnamese victims, and others around the world who believe they have medical problems caused by Agent Orange? Martini draws on military records, government reports, scientific research, visits to contaminated sites, and interviews to disentangle conflicting claims and evaluate often ambiguous evidence. He shows that the impact of Agent Orange has been global in its reach affecting individuals and communities in New Zealand, Australia, Korea, and Canada as well as Vietnam and the United States. Yet for all the answers it provides, this book also reveals how much uncertainty - scientific, medical, legal, and political - continues to surround the legacy of Agent Orange."--Project Muse.